Factors associated with emergency nurses' practices towards disaster management - Ahayalimudin, Nurul'Ain; Osman, Nor Naimah Saidah (2015)
Introduction: Disasters kill thousands of people and damage huge numbers of habitat and properties each year, which gives a big impact to the community involved. Therefore, the fundamental of disaster management is important for emergency nurses as frontline, where its understanding will reduce the impact of disaster and its aftermath. Objective: To identify factors that contributes to emergency nurses’ practice towards disaster management. Methodology: This cross-sectional study design has been carried out between March and May 2013. The data were collected from 65 (100%) emergency nurses in 3 public hospitals of East Coast region. Questionnaire developed by Nurul’Ain (2012) ‘KAP towards disaster management’ was utilised and the data were analysed by using Chi-square and Fisher Exact test. Results: Merely 60% (n=39) of emergency nurses had shown adequacy in their practice towards disaster management. Of 65 emergency nurses involved in this study, the majority of nurses with age of 30 and above (41.5%, n=27) demonstrate their adequacy in practice towards disaster management. In regards to level of education, about 35 (59.3%) emergency nurses with diploma and of 43 emergency nurses graduated in year 2000 and above, about 26 (60.5%) shows their adequacy in practice. It have been statistically proven that their working experience in emergency settings (p=0.013), involvement in disaster response (p< 0.001) and attended disaster education (p< 0.001) are significantly associated with their practice. Conclusion: It has been recognised that emergency nurses were lacking in regards to practices towards disaster management. These research outcomes may beneficial to strengthen their practices. With the enforcement from the health care institutions in regards to conducting frequent education/training perhaps emergency nurses can be prepared in advance while dealing with disaster victims. Keywords: Disaster management; Disaster; Emergency nurses; Practices; Public hospital